Selected Topics on Socio-technical Perspective in Information Systems: Editorial Introduction to Issue 18 of CSIMQ - Peter Bednar; Ilia Bider (Complex Systems Informatics and Modeling Quarterly)
This thematic issue of the Complex Systems Informatics and Modeling Quarterly journal is dedicated to using a socio-technical perspective in the Information Systems (IS) field. It contains a selection of extended papers presented at STPIS'18 – 4th International Workshop on Socio-Technical Perspective in IS Development held on June 12, 2018 in Tallinn, Estonia. The articles presented in this thematic issue contain at least 30% new material compared to the initial papers. After the extension, all articles went through two rounds of reviews to ensure the quality of the papers published in this issue. STPIS papers cover both theoretical and practical aspects of using a socio-technical perspective in IS, which is reflected in the current issue that contains both theoretically and practically oriented papers.